Prospects for the Development of Electronic Resources for Social and Communication Activities of Information Institutions in Ukraine and the World - Ігор Бондар (Цифрова платформа: інформаційні технології в соціокультурній сфері, 2022)
The purpose of the article is to study the prospects of the development of electronic resources for social and communication activities of information institutions in Ukraine and the world.